Morphological variation in Bolitoglossa vallecula (Amphibia: Caudata: Plethodontidae) in the Cordillera Central of Colombia (2011)
ABSTRACT: Body size and head shape variation was quanti ed in four populations of Bolitoglossa vallecula in the Cordillera Central of Colombia. two of these four populations occurred in sympatry with B. ramosi, an ecologically similar salamander species that could potentially compete with B. vallecula for food resources. there was no evidence of sexual size or head shape dimorphism in any population, so data for males and females were pooled. the populations differed signi cantly in mean body size, but this variation was not associated with elevation. Six head shape characteristics associated with head morphology were quantified and analyzed using the ratio of each variable over the geometric median, given that this is the most preferred method in the literature for describing conformation while controlling for the effects of size. One of the populations sympatric with B. ramosi (Bello) exhibited signficant differences in conformation of head morphology when compared to the allopatric populations, while the other sympatric population did not. While the evidence for character displacement due to ecological competition was equivocal, the analyses highlight areas where further research should be directed.